ANALYSIS OF THE NEEDS OF COGNITIVE CONFLICT-BASED TEACHING MATERIALS INTEGRATED WITH AUGMENTED REALITY ON LIGHT WAVE - Tika, Luth Fiyyah Atiqah; Mufit, Fatni (Department of Physics Universitas Negeri Padang, 2024)
21st century learning demands student centered learning and requires integration of technology in learning including augmented reality (AR) technology. This study aims to determine the needs of teachers and students for cognitive conflict-based teaching materials that are integrated with augmented reality (AR) so as to increase student understanding and reduce misconceptions that occur in light wave material. This type of research is preliminary research. The instrument used was a questionnaire regarding the needs of learning devices and the implementation of physics learning as well as journal analysis of students' conceptual understanding of the material of light waves. This test was conducted at several schools in the city of Padang with a total of 130 students and 3 teachers. The results of the study stated that learning was still centered on the teacher and there was no learning model to overcome misconceptions and there was no teaching material integrated with augmented reality (AR). The results of the journal analysis concluded that students' understanding of the concept of light waves was still low. Therefore, it is necessary to develop cognitive conflict-based teaching materials integrated with augmented reality (AR) on light waves in accordance with 21st century learning.